Anti-inflammatory effects of Lactobacillus plantarum CRL 759 supernatant in ocular inflammations - Layús, Barbara Ivana (2019)
Anti-inflammatory effect of probiotic bacteria cell free supernatant was extensively proved as therapy for different inflammatory diseases, but no investigated in ocular inflammatory disorders. Uveitis, an intraocular inflammatory disease, is a common cause of vision loss. Traditional treatments with corticosteroid present several side effects, and alternative therapies are continuously investigated.The aims of this study were to evaluate whether Lactobacillus plantarum CRL 759 supernatant (LplS) was able to diminish the inflammatory response triggered by LPS in ARPE-19 cells (human retinal pigment epithelium cell line); in addition, to evaluate in vivo its capacity to exert anti-inflammatory effect in uveitis induced by endotoxin in mice.L. plantarum CRL 759 was cultured in DMEM medium at 37ºC and 5% CO2. LplS was obtained by filtration with 0.22 μm membranes. ARPE-19 cells (2.5x105) were treated with LplS 4 h; then, the cells were stimulated with LPS (10 µg/ml). Cytokines (by flow cytometry), NO and TBARS (by colorimetric methods) produced by ARPE-19 cells were measured in the culture supernatant.To induce uveitis, 130 µg LPS was injected subcutaneously into C57BL/6 mice. LplS was administered as drops and Prednisolone (P) was used as anti-inflammatory control. The mice were divided into six groups randomly: LPS group (LPS injection + PBS drops); LPS + LplS group (LPS injection + LplS drops); LPS + P group (LPS injection + prednisolone drops) and control groups: treated with PBS, LplS or P drops and a PBS injection. 24 hours after stimulation with LPS or PBS, mice were sacrificed. The ocular inflammation was assessed by slit lamp microscopy and clinical scores were determined at the same time. The aqueous humor (AqH) was collected and total protein (by Bradford assay), TNF-α level (by ELISA), and cell count (by Giemsa coloration) were determined. Eyes were enucleated to histopathologic evaluation.Results showed that LplS reduced the production of IL-6, IL-8, NO and TBARS in LPS-stimulated ARPE-19 cells. In vivo studies, the clinical score of mice treated with LplS drops was significantly lower than the LPS group. LplS also reduced levels of TNF-α and protein concentration in AqH. Histological examination showed reduction of infiltrating inflammatory cells in the posterior segment of LPS + LplS group; however, there was no significant difference in leukocyte count in AqH in all groups. LplS anti-inflammatory effect was similar to that induced by prednisolone. In this study, we showed that LplS as ophthalmic drops attenuates the inflammatory process in an endotoxin-induced uveitis. These effects were comparable to the one achieved by prednisolone, and could be proposed as a potential therapy for ocular inflammatory disorders.